The role of psychological capital in female leadership development in the Malaysian public sector - Abdul Manaf, Nurul Huda (2025)
This study explores the pivotal role of Psychological Capital (PsyCap) in empowering female leaders within the Malaysian public sector through a basic qualitative research methodology. PsyCap, encompassing self-efficacy, optimism, hope, and resilience, is increasingly recognised as a critical factor in enhancing leadership capabilities and fostering organisational effectiveness. Despite ongoing efforts towards gender parity, female leaders often encounter unique obstacles that can impede their professional advancement and leadership efficacy. This research seeks to deepen the understanding of how PsyCap can help mitigate these challenges and promote leadership excellence among women. This study addresses the gap by providing the dimensions of PsyCap and the motivation for female leadership development in the public sector. It has explored the key dimensions of PsyCap, factors of female leaders' motivation, and female leadership resiliency in the context of the Malaysian public sector. The study is grounded in psychological capital, social role theory, and transfor-sactional leadership theory. It involves in-depth semi-structured interviews and a focus group discussion with 23 female leaders at mid- and premier-level positions across various public sector organisations, capturing rich insights into their experiences and the strategies they employ to harness their PsyCap professionally. A thematic analysis using NVivo was applied to identify the study's themes. The first finding indicates that high levels of PsyCap elements in hope, efficacy, resilience and optimism (H.E.R.O) are instrumental in enhancing the effectiveness of female leaders' leadership in the public sector. Resilience is the most outstanding pattern. Resilience is demonstrated in proactive decision-making and problem-solving, standing firm against negativity, balancing work and personal life, and learning and growing through adversity. Hope is secondly mentioned, emphasises the vision for subordinates' growth and welfare and is driven by accountability. The second finding indicates that participants are motivated to sustain themselves in the public sector due to agility behaviour and career establishment to serve the public. Agility underscores vital internal qualities crucial for effective leadership: integrity, accountability, professionalism, self-confidence, resilience, and a commitment to continuous learning. Establishing a successful career requires practical strategies and tools, including self-awareness assessments and skill-building opportunities. Female leaders’ leadership resiliency is shown as the third finding, based on their ability to have emotional adaptability, be performance-oriented, and lead with integrity. These are key competencies necessary for effective leadership, particularly for female leaders within the public sector. The female leadership framework emphasises that female multidisciplinary psychological capital attributes, female leadership motivation and female leadership resiliency can work synergistically to empower women leaders in the Malaysian public sector. This research highlights the importance of developing and empowering PsyCap among female leadership skills. Thus, public sector organisations can foster these psychological resources to support female leaders' personal and professional growth. Ultimately, this research contributes authoritative insights to the discourse on psychological capital, gender equality and leadership development, offering a robust framework for advancing female leadership in the Malaysian public sector.